Dark Mode

458 views

6 votes

Best answer

For this we need to find the corresponding characteristic equation which will be cubic :

This is found as :

| A - λ I | = 0

==> (1 - λ)[ (5 - λ)(1 - λ) - 1 ] + 1 [ 3 - 1 + λ ] + 3 [ 1 - 3(5 - λ) ] = 0

==> λ^{3} - 7λ^{2} + 36 = 0 which is the required characteristic equation of the given matrix..

Now using relation between roots and coefficients , we have :

Sum of roots taken two at a time = (Coefficient of λ ) / (Coefficient of λ^{3}) = 0

Product of roots = -(Constant term) / (Coefficient of λ^{3}) = -36

But here it is -αβγ = -(-36) = 36

**Hence 36 is the correct answer..**